Armyworm (Spodoptera frugiperda J.E. Smith) Attack And Pest Population On Several Hybrid Corn Varieties And Strains In Talawaan Village, Talawaan District - Threis Umboh; Christina L. Salaki; Dantje Tarore (Jurnal Agroekoteknologi Terapan, 2023)
New superior varieties and high-yielding maize lines are one of the main components of the technology for increasing maize production. This study aims to determine the larval population and pest attack of S. frugiperda on two varieties and eight lines of hybrid maize implemented in Talawaan Village. It is hoped that from this study information on larval populations and pest attacks of S. frugiperda on two varieties and eight lines of hybrid maize implemented in Talawaan Village will be obtained. This study used a randomized block design with 10 treatments, consisting of two varieties and eight lines, each treatment was repeated 3 times, so that 30 experimental units were obtained. As treatments were two maize varieties, namely ADV 777 (A) and JH 37 (J) and eight lines namely HLN 01 (B), HLN 02 (C), HLN 03 (D), HLN 04 (E), HLN 05 ( F), HLN 06 (G), HLN 07 (H), HLN 08 (I). Observations were made at intervals of 1 week starting at 15 ADP, 22 ADP, 29 ADP and 36 ADP.  The things that were observed were attack symptoms, larval populations and the percentage of S. frugiperda in the treatments being tested. The results showed that the highest average population of S. frugiperda larvae was found in the 36 ADP observations, namely treatment I (HLN 08) namely 165.33 individuals and the lowest in treatment A (ADV 777) of 18.33 individuals. The highest percentage of attacks was observed at 36 ADP, namely treatment I (HLN 08) of 46.00% and the lowest in treatment A (ADV 777) of 11.00%. Keywords: varieties, lines, S. frugiperda, corn hybrid Abstrak Varietas unggul baru dan galur tanaman jagung yang berdaya hasil tinggi merupakan salah satu komponen utama teknologi peningkatan produksi jagung.  Penelitian ini bertujuan untuk menganalisis populasi larva dan serangan hama S. frugiperda pada dua varietas dan delapan galur jagung hibrida yang dilaksanakan di Desa Talawaan.  Diharapkan dari penelitian ini dapat diperoleh informasi populasi larva dan serangan hama S. frugiperda pada dua varietas dan delapan galur jagung hibrida yang dilaksanakan di Desa Talawaan.  Penelitian ini menggunakan Rancangan Acak Kelompok dengan 10 perlakuan, yang terdiri dari dua varietas dan delapan galur, masing-masing perlakuan diulang 3 kali, sehingga diperoleh 30 satuan percobaan.  Sebagai perlakuan adalah dua varietas jagung, yakni ADV 777 (A) dan JH 37 (J) dan delapan galur yaitu HLN 01 (B), HLN 02 (C), HLN 03 (D), HLN 04 (E), HLN 05 (F), HLN 06 (G), HLN 07 (H), HLN 08 (I).  Pengamatan dilakukan selang periode 1 minggu yang dimulai pada 15 HST, 22 HST, 29 HST dan 36 HST.  Hal-hal yang diamati adalah gejala serangan, populasi larva dan persentase serangan S. frugiperda pada perlakuan yang diujicobakan.  Hasil penelitian menunjukkan bahwa rataan populasi larva S. frugiperda tertinggi dijumpai pada pengamatan 36 HST yaitu perlakuan I (HLN 08) yakni 165.33 ekor dan terendah pada perlakuan A (ADV 777) sebanyak 18.33 ekor.  Persentase serangan tertinggi pada pengamatan 36 HST yakni perlakuan I (HLN 08) sebesar 46.00% dan terendah pada perlakuan A (ADV 777) sebesar 11.00%. Kata kunci : varietas, galur, Spodoptera frugiperda, jagung hibrida